Synthesis and Characterization of Urethane Side Chain Substituted Diketopyrrolopyrrole - Dharmapurikar, S.; Aher, J.; Puyad, A.; Kakade, G. K.; Kalalawe, V. G.; Kanetkar, M. V. (Journal of Scientific Research, 2021)
The synthesis of Diketopyrrolopyrrole (DPP) having secondary interaction in the side chain explores its possibility to use in electronic and sensing applications. Herein we report easy method to engineer side chains of DPP. The hydrogen bonding is introduced on the side chain by substitution of urethane side chains on Diketopyrrolopyrrole (DPPurethane).The urethane side chain comprises a branched alkyl chain with good yields and purities. The DPPurethane characterized by NMR and IR, optical properties along with energy minimized structure were studied.